FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA ANAK USIA 1-5 TAHUN - Sumiyati, Iis (Journal of Midwifery Tiara Bunda, 2025)
The inhibiting factor in breastfeeding is the lack of milk production and the slow release can cause the mother not to give her baby enough. A small amount of breast milk production in the first days of childbirth is an obstacle in breastfeeding. This problem can be solved by doing oxytocin massage. Oxytocin massage serves to stimulate the secretion of oxytocin which stimulates the secretion of breast milk. Breastfeeding is one of the pillars that are important for baby’s health because breast milk is the most appropriate nutrition for newborn babies to a minimum of 6 months old babies. This study aims to determine the effect of oxytocin massage on breast milk production in postpartum mothers in the working area of independent practice of midwives “X” in Bekasi City, West Java in 2024. This type of research was quantitative with a Quasy experimental design. The population in this study were all postpartum mothers who experienced unsustainable breastfeeding in the Working area of independent practice of midwives “X” in Bekasi City, West java 2024 a total of 27 mothers. The sample consisted of 25 mothers with the Wilcoxon Test. The independent variable is fluency before oxytocin massage. The dependent variable is the fluency of breastfeeding after oxytocin massage in postpartum mothers. Collecting data using observation sheets and questionnaires. Data processing techniques used editing, coding, scoring, tabulating and statistical tests using the Wilcoxont statistical test. The results of this study were obtained from 25 respondents, the average fluency of breastfeeding in postpartum mothers before the oxytocin massage in the working area of independent practice of midwives “X” in Bekasi City, West Java in 2024 was 17 mothers (68%) (less fluent), while the average fluency of breastfeeding in postpartum mothers after the oxytocin massage in The working area of independent practice of midwives “X” in Bekasi City, west Java in 2024 is 25 mothers (100%)(Current). Wilcoxon shows that the p value = o, ooo